INTEGRATION OF DIGITAL COMMUNICATION IN SUSTAINABLE SHARIA FINANCE : CHALLENGES AND OPPORTUNITIES IN THE CYBER MEDIA ERA - Kurniawati, Juliana; Fitria Yuliani; Sri Dwi Fajarini (International Journal of Accounting Innovation, 2025)
Objective: This study aims to examine the challenges and opportunities faced by the Islamic finance sector in utilizing digital communication technology. Method: This article uses a qualitative research method based on a literature review, analyzing the integration of digital communication in Islamic banking services and the implementation of digital technology, as well as opportunities and challenges in the cyber media era. Results: On the one hand, the use of digital platforms expands access to Islamic financial services, increases transparency, efficiency, and community involvement. However, on the other hand, a number of challenges arise, including low digital literacy, cybersecurity threats, and the need for regulations that are in accordance with sharia principles. Novelty: With a deeper understanding, the integration of digital communication can be a strong basis for strengthening inclusive, adaptive, and sustainable sharia finance amidst the changes in the digital era. Utilizing all available resources on the internet for the integration of sharia banking product services, for example creating interesting content on digital media platforms as a means of promotion and education for Indonesian society.